High speed internet development in Africa using 4G-LTE technology-a review - Mohamed Njikam; Nanna S.; Shahrin S.; Mohd Fairuz Iskandar Othman (Bulletin of Electrical Engineering and Informatics, 2019)
The African continent is ranked second most populated region and has a huge amount of natural resources to be locally transformed or outsourced overseas. The traditional telecommunications system has helped connect people and enabled them to manage their businesses and trading in Africa for a long-time; many African countries have embarked early in changing their network and technology systems during the first years of the information age. Over a few decades ago, the introduction of new telecommunication methods and techniques have influenced much of African countries’ growth via different perspectives. The situation has triggered an enormous interest in people. They analyzed the factors supporting such changes, which in the case of this paper is all about the advent and adoption of LTE/4G-LTE technologies including its service commercialization in Africa. This review article attempts to provide an overview of 4G-LTE networks technologies and the internet; it includes the current evolution of telecommunication networks within and even beyond the African continent, assisted by the 4G-LTE expansion. An extended view is provided throughout this article’s development with respect to what could be expected (or is missing) for the sake of this continent’s telecommunication infrastructure enhancement and a better QoS to Africa’s dwellers.